Chitin scar breaks in aged Saccharomyces cerevisiae - Powell, Chris D; Quain, David E; Smart, Katherine A (Microbiology (Society for General Microbiology), 2003)
1 School of Biological and Molecular Sciences, Oxford Brookes University, Headington, Oxford OX3 0BP, UK 2 Coors Brewers, Technical Centre, PO Box 12, Cross Street, Burton-on-Trent DE14 1XH, UK Correspondence Katherine A. Smart kasmartatbrookes.ac.uk Ageing in budding yeast is not determined by chronological lifespan, but by the number of times an individual cell is capable of dividing, termed its replicative capacity. As cells age they are subject to characteristic cell surface changes. Saccharomyces cerevisiae reproduces asexually by budding and as a consequence of this process both mother and daughter cell retain chitinous scar tissue at the point of cytokinesis. Daughter cells exhibit a frail structure known as the birth scar, while mother cells display a more persistent bud scar. The number of bud scars present on the cell surface is directly related to the number of times a cell has divided and thus constitutes a biomarker for replicative cell age. It has been proposed that the birth scar may be subject to stretching caused by expansion of the daughter cell; however, no previous analysis of the effect of cell age on birth or bud scar size has been reported. This paper provides evidence that scar tissue expands with the cell during growth. It is postulated that symmetrically arranged breaks in the bud scar allow these rigid chitinous structures to expand without compromising cellular integrity. Abbreviations: SEM, scanning electron microscopy; WGA, wheat-germ agglutinin